El Salvador : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for El Salvador. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
El Salvador's 2008 Article IV Consultation examines the country's economic developments and policies. In 2007, the fiscal position improved, the public debt-to-GDP ratio declined, and economic growth reached its highest level in a decade. The rise in global commodity prices has also generated substantial inflation pressures. The stock of bank deposits has stagnated relative to end-2007, while deposit rates have increased slightly. Interbank repo rates have also risen recently, reflecting tighter funding conditions, and banks have increased their external borrowing, in part to build up liquidity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet